Genome-Wide Identification and Characterization of ITCP/I Gene Family Members in IMelastoma candidum/I - Li, Hui; Wen, Xiaoxia; Huang, Xiong; Wei, Mingke; Chen, Hongpeng; Yu, Yixun; Dai, Seping (Molecules (Basel, Switzerland), 2022)
It has been confirmed that the plant-specific Teosinte-branched 1/Cycloidea/Proliferating (TCP) gene family plays a pivotal role during plant growth and development. M. candidum is a native ornamental species and has a wide range of pharmacodynamic effects. However, there is still a lack of research on TCP’s role in controlling M. candidum’s development, abiotic stress responses and hormone metabolism. A comprehensive description of the TCP gene family in M. candidum is urgently needed. In this study, we used the HMMER search method in conjunction with the BLASTp method to identify the members of the TCP gene family, and a total of 35 TCP genes were identified. A domain analysis further confirmed that all 35 TCPs contained a TCP superfamily, a characteristic involved in dimerization and DNA binding that can be found in most genes from this gene family, suggesting that our identification was effective. As a result of the domain conservation analysis, the 35 TCP genes could be classified into two classes, TCP-P and TCP-C, based on the conservative regions of 55 and 59 amino acids, respectively. Gene-duplication analysis revealed that most TCP genes were present in duplication events that eventually led to TCP gene expansion in M. candidum. All the detected gene pairs had a Ka/Ks value of less than one, suggesting that purification selection is the most important factor that influences the evolution of TCP genes. Phylogenetic analysis of three species displayed the evolutionary relationship of TCP genes across different species and further confirmed our results. The real-time quantitative PCR (qRT-PCR) results showed that McTCP2a, McTCP7a, McTCP10, McTCP11, McTCP12a, McTCP13, McTCP16, McTCP17, McTCP18, McTCP20 and McTCP21 may be involved in leaf development; McTCP4a, McTCP1, McTCP14, McTCP17, McTCP18, McTCP20, McTCP22 and McTCP24 may be involved in flower development; and McTCP2a, McTCP3, McTCP5a, McTCP6, McTCP7a, McTCP9, McTCP11, McTCP14 and McTCP16 may be involved in seed development. Our results dissect the TCP gene family across the genome of M. candidum and provide valuable information for exploring TCP genes to promote molecular breeding and property improvement of M. candidum in the future.